The Sultan Center - AlNuwaif, Maryam; Edrees, Sara (Journal of The Community Development in Asia, 2019)
What makes â€œthemâ€ the best? The purpose of this research is to enhance what makes sultan center different from all the other supermarkets. Sultan center has been successful, doesnâ€™t it make you wonder, how are they successful? â€œIt is because they use good performance management?â€ This research is going to include what is sultan center, and we will interview their manager to have full feedback about their company, how they work, mission/vision, goals and market segment. As we as how did they accomplish having loyal customers and how they manage to overcome their competitors. In the interview, we will reveal more of sultan center secrets and their great success.